Resilience, Decision-Making And Risk Behaviors Among Early Adolescents In Penang - Loke, Wai Chuen (2018)
Resilience is the ability of individuals to tap into the available resources to increase the likelihood of positive adaptation and reduce the probability of disturbances in functioning in the face of adversity (Goldstein & Brooks, 2012; Masten, 2014; Ungar, 2013).The present study sought to determine the relationship between resilience and risk behaviors among early adolescents with decision-making acting as a mediator. Form 1 and Form 2 students (N = 65) were recruited at a high-needs school in Penang.